Sex differences in neonatal brain injury and inflammation - Kelly, Lynne A.; Branagan, Aoife; Semova, Gergana; Molloy, Eleanor J. (Frontiers in Immunology, 2023)
Neonatal brain injury and associated inflammation is more common in males. There is a wellrecognised difference in incidence and outcome of neonatal encephalopathy according to sexgender with a pronounced male disadvantage. Neurodevelopmental differences manifest from an early age in infancy with females having a lower incidence of developmental delay and learning difficulties in comparison with males and male sex has consistently been identified as a risk factor for cerebral palsy in epidemiological studies. Important neurobiological differences exist between genders the sexes with respect to neuronal injury which are especially pronounced in preterm neonates. There are many potential reasons for these sex differences including genetic, immunological and hormonal differences but there are limited studies of neonatal immune response. Animal models with induced neonatal hypoxia have shown various sex differences including an upregulated immune response and increased microglial activation in males. Male sex is recognized to be a risk factor for neonatal hypoxic ischemic encephalopathy (HIE) during the perinatal period and this review discusses in detail the sex differences in brain injury in preterm and term neonates and some of the potential new therapies with possible gender sex affects.